Pengelolaan Citra Digital ( Perbandingan Studi Kasus Antara Klasifikasi Warna Menggunakan Pengolahan Model Warna HSV Dan Penerapan Metode Konvolusi Dalam Pengolahan Citra Digital ) - Naufal, Daffa Handika; Rahmadewi, Reni (Jurnal Ilmiah Wahana Pendidikan, 2024)
The research conducted by the researcher is to compare the Case Study of Color Classification Using Hsv Color Model Processing and the Application of Convolution Methods in Digital Image Processing, which later obtained different conclusions but one goal is effectiveness and efficiency in two different models of digital image management. The research method in this study uses descriptive qualitative methods where by comparing the research data obtained in two studies, namely Color Classification Using Hsv Color Model Processing and Application of Convolution Methods in Digital Image Processing. A more effective test result according to the author is using the Convolution method where Convolution provides a way to combine two arrays, usually for different array sizes, but for the same array dimensions, resulting in a third array that has the same dimensions.